PARTISIPASI ANGGOTA RESIMEN MAHASISWA DALAM PENGELOLAAN LINGKUNGAN HIDUP DI KOTA MAKASSAR - ASTI, A. SYAMSUL ([Yogyakarta] : Universitas Gadjah Mada, 2012)
A. Syamsul Asti: Members of Regiment Student Participation In Environmental Management in Makassar. Thesis, Jogjakarta: Graduate School, Universitas Gadjah Mada, 2011. The research was conducted in Makassar in order to analyze the participation of members of the regiment students in environmental management in Makassar, South Sulawesi. To analyze the factors that influence the level of participation of members of the regiment student in environmental management in Makassar. The method used in this study is a quantitative method. The data was collected using a questionnaire survey, in-depth interviews, and documentation as support. Determination of the samples was done by using census, conducted the analysis in this study to determine the level of the regiment's participation in environmental management students with descriptive analysis method with intervals of low-level scoring technique, medium, high by the number of samples as many as 150 members of the regiment of students and to determine the effect of socioeconomic Participation rates are used to cross tabulation end correlation. The analysis result from the tabulation shows each other that the participation level of the student regiment member in the management of the life environment in Macassar city is grouped in the middle category, that is 60%. The result of the analysis through pearson correlation of the moment product shows that the influence of the parent's status - 0,11, the work influence -0,12, income influence - 0,06, and the education influence - 0,39, so it can be conclude that the background of the family has insignificant influence toward the participation level of the student regiment member in the management of the life environment in Macassar city.